2012
DOI: 10.1007/s00192-012-1841-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of clinical parameters, cystourethroscopy, and magnetic resonance imaging in the preoperative diagnosis of urethral diverticula

Abstract: These data reinforce the utility of transurethral fluid expression for preoperative evaluation of urethral diverticula. Additionally, MRI is an excellent adjunctive diagnostic tool and may assist in establishing the diagnosis when there is high clinical suspicion of a urethral diverticulum but nonconfirmatory findings on cystourethroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…However, good agreement was noticed between major urethral abnormalities on TLUS and the diagnosis of UD on urethroscopy, with a sensitivity of 100% and a specificity of 99.8% for the diagnosis of UD on ultrasound when using urethroscopy as the gold standard. The latter is highly specific for diagnosing UD, nevertheless, it has variable reported sensitivities, as the test is largely operator-dependent, and small diverticular ostia can easily be overlooked 3,5,17 . We believe that a high degree of suspicion following TLUS might increase the sensitivity and accuracy of urethroscopy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, good agreement was noticed between major urethral abnormalities on TLUS and the diagnosis of UD on urethroscopy, with a sensitivity of 100% and a specificity of 99.8% for the diagnosis of UD on ultrasound when using urethroscopy as the gold standard. The latter is highly specific for diagnosing UD, nevertheless, it has variable reported sensitivities, as the test is largely operator-dependent, and small diverticular ostia can easily be overlooked 3,5,17 . We believe that a high degree of suspicion following TLUS might increase the sensitivity and accuracy of urethroscopy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Aside from being invasive procedures that are uncomfortable for the patient, these studies can only detect diverticula that have sizeable and patent communication with the urethra. Diverticula with thin connection, as well as alternate diagnoses, are unlikely to be detected using this type of imaging [12,13]. MRI not only helps diagnose the diverticulum but also helps detect any associated complications, such as superimposed infections, presence of calculi , or malignant transformation [14].…”
Section: Urethral Diverticulummentioning
confidence: 99%
“…In the study of Lee et al [4], the sensitivity of cystourethroscopy was 71.4%, and in the study of Pathi et al [11], the sensitivities, specificities, positive predictive values (PPVs) and negative predictive values (NPVs) of cystourethroscopy were 33, 100, 100 and 42%, respectively. Similar to the study of Pathi, the sensitivity of cystourethroscopy in our group was only 40% (4 for 10).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed the sensitivity, specificity, PPV and NPV of MRI for diagnosis of UD to be 100, 83, 9, and 100%, respectively [11]. However, another study showed that 24.4% of UD patients, diagnosed by MRI, had some discrepancy between the operative findings and the images of MRI, which made the search for the ostia difficult [17].…”
Section: Discussionmentioning
confidence: 99%